Activity settings in toddler classrooms and quality of group and individual interactions - Guedes, C.; Cadima, J.; Teresa, A.; Aguiar, C.; Barata, C. (Journal of Applied Developmental Psychology, 2020)
This study examined the variation of interaction quality both at the group and child levels across different activity settings in toddler classrooms. Participants were 104 children, with an average of 30.4 months old, of which 53.8% were boys. Educator-child interactions, at the group level, and child interactions with their educators, peers and tasks, at the child level, were observed through video-recordings across four activity settings, namely free play, early academic activities, aesthetics/arts activities and meals. Group level interactions were observed with the CLASS Toddler, and child level interactions with the inCLASS Toddler. Results showed that the quality of interactions at the group and child levels varied across different activity settings, but not always in the same direction. Findings suggest that activity settings play an important role in explaining the quality of interactions experienced by toddlers. Implications for early childhood educators are discussed.